Tropical grasslands: A pivotal place for a more multi-functional agriculture - Boval, Maryline (Ambio, 2016)
Tropical grasslands represent a pivotal arena for the sustainable intensification of agriculture in the coming decades. The abundant ecosystem services provided by the grasslands, coupled with the aversion to further forest destruction, makes sustainable intensification of tropical grasslands a high policy priority. In this article, we provide an inventory of agricultural initiatives that would contribute to the sustainable intensification of the tropical grassland agro-ecosystem, and we recommend a shift in the scientific priorities of animal scientists that would contribute to realization of a more agro-ecological and multi-functional agriculture in the world’s tropical grasslands.